HEALTHCARE ACCESS AND EQUITY: ADDRESSING DISPARITIES IN KENYA - Ndingi, Kennedy (UoEm, 2024)
This paper embarks on exploring the inequity in access to healthcare in Kenya. This is despite the efforts by the government to ensure that all citizens have equal access to health. This paper suggests that the tremendous steps taken by the government towards that direction have been hampered by inconsistencies. The study aims to tackle social-economic disparities that negatively influence access to healthcare. A special focus is illuminated on the prevalence of socio-economic inequalities in the country. Poverty, poor quality of health services, inadequate medical personnel, inaccessibility to healthcare services and geographical barriers are some of the disparities that the paper addresses. This paper also analyses the Universal Health Coverage Policy that contains strategies and framework for implementation of health policy from the year 2020 to the year 2030. Furthermore, this study looks into the role played by both the government and stakeholders in the Heath Sector. Through the lenses of this paper the government has a critical role to play to ensure equitable access to health care services to its citizens.
Keywords: HEALTHCARE ACCESS AND EQUITY